Preservice Teachers’ Perceptions of Intercultural Communicative Competence: A Pathway to Peace and 21st Century Skills in Nepal - Kadel, Purna Bahadur (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
Intercultural communicative competence is an essential attribute and phenomenon to maintain harmony and a sense of cosmopolitanism in a diverse and heterogeneous society like Nepal. This study explored preservice teachers’ perceptions of the importance of intercultural communicative competence and what specific 21st-century skills are enhanced by intercultural communicative competence. In order to address the research questions, the hermeneutic phenomenological research design was adopted to carry out this study. The in-depth- interview was administered as a tool to collect the lived experiences of the participants. Eight preservice teachers were selected from 4 strata: madheshi community, ethnic community, untouchable community, and brahmin community as participants for this study. The findings of this study were maintaining peace and promoting social cohesion, developing global citizens, prescribing ICC in school curriculum, blessing ICC for heterogeneous society, promoting ICC through English and Nepali languages, and enhancing 21st-century skills by ICC. Intercultural communicative competence plays a significant role in promoting human civilization, confidence, and sense of security in the society.